From Specific γ‐CD/[Nb6Cl12(H2O)6]2+ Recognition to Biological Activity Tuning. Issue 33 (19th May 2020) - Ivanov, Anton A.; Pozmogova, Tatiana N.; Solovieva, Anastasiya O.; Frolova, Tatiana S.; Sinitsyna, Olga I.; Lundovskaya, Olga V.; Tsygankova, Alphiya R.; Haouas, Mohamed; Landy, David; Benassi, Enrico; Shestopalova, Lidiya V.; Falaise, Clément; et al.
Abstract: Specific molecular recognition of γ‐cyclodextrin (γ‐CD) by the cationic hexanuclear niobium [Nb6 Cl12 (H2 O)6 ] 2+ cluster complex in aqueous solutions results in a 1:1 supramolecular assembly [Nb6 Cl12 (H2 O)6 ]@γ‐CD 2+ . NMR spectroscopy, isothermal titration calorimetry (ITC), and ESI‐MS were used to study the interaction between the inorganic cluster and the organic macrocycle. Such molecular association affects the biological activity of [Nb6 Cl12 (H2 O)6 ] 2+, decreasing its cytotoxicity despite enhanced cellular uptake. The 1:1 stoichiometry is maintained in solution over a large window of the reagents' ratio, but crystallization by slow evaporation produces a 1:2 host–guest complex [Nb6 Cl12 (H2 O)6 @(γ‐CD)2 ]Cl2 ⋅ 20 H2 O featuring the cluster encapsulated between two molecules of γ‐CD. The 1:2 complex was characterized by XRD, elemental analysis, IR spectroscopy, and thermogravimetric analysis (TGA). Quantum chemical calculations were performed to model host–guest interaction. Abstract : Welcome ! Specific molecular recognition of γ‐cyclodextrin (γ‐CD) by the [Nb6 Cl12 (H2 O)6 ] 2+ niobium cluster complex in aqueous solutions results in a 1:1 supramolecular assembly [Nb6 Cl12 (H2 O)6 ]@γ‐CD 2+ . Crystallization results in a 1:2 host–guest complex [Nb6 Cl12 (H2 O)6 ]@(γ‐CD)2 Cl2 ⋅20 H2 O. The molecular association affects the biological activity of [Nb6 Cl12 (H2 O)6 ] 2+ . Quantum chemical calculations were performed to model host–guest interaction.